Med komunikacijskim in problemsko-ustvarjalnim poukom književnosti - Medved-Udovič, Vida (Jezik in slovstvo, 2015)
The paper sheds light on the teaching of literature in primary schools and identifies the communication model of bringing literature closer to young readers from the first to the ninth grade as the central approach to implementing this objective. It proposes that, in the second and especially in the third education cycle, this should be upgraded with elements of systemic didactics and problem-solving and creative teaching. In discussing literary texts, it points to the significance of the interpretation of less-known vocabulary and analyses a survey questionnaire carried out with fourth-year students at the Koper Faculty of Education, on the basis of which students' attitudes towards the topics discussed in the paper were acquired.
Keywords: didaktika književnost; bralna zmožnost; učni načrti; Slovene; slovenščina; osnovne šole